The Influence of Energy Resources in Developing "Pragmatic" Relations Between Azerbaijan and the West - Sabina Strimbovschi (CES Working Papers, 2016)
The aim of the paper is to research the way energy resources shaped Azerbaijan's foreign policy and contributed to developing its strategic relations with western actors trying, at the same time, to bring arguments whether or not the democratic deficit in Azerbaijan is related to the”resource nationalism”. The author makes a retrospective analysis of the most important events that have influenced Azerbaijan's foreign policy since the collapse of USSR. In this regard, it is assessed the impact of the “Contract of the Century” on the evolution of the country, forasmuch the signing of the document is considered the first strategic move made by Azerbaijan since 1991. Because Nagorno-Karabakh is a crucial priority for the country's territorial integrity, it is examined the manner in which Azerbaijani authorities are trying to make use of the energy resources projects in order to speed up the settlement of the protracted conflict, but without success so far. Last but not least, are analysed the EU-Azerbaijan relations, both on the energy and political level, highlighting on the one hand, the reluctance of Azerbaijan towards the democratic reforms promoted within the Eastern Partnership, but on the other hand, the interest of Baku to negotiate the unwanted agreements with Brussels, counting on its advantage as a supplier of energy resources on the European market. Consequently, some key questions have emerged: Is the EU's strategic objective to ensure its energy security more important than promoting and encouraging its partners to adopt the fundamental values of the EU? What impact may have the Strategic modernization partnership on the EU-Azerbaijan relations? Is European Union's credibility in danger, by having so diverse approaches towards the Eastern Partnership countries?
Keywords: 330; Democracy; energy; European Union; Azerbaijan; Nagorno-Karabakh